Un artista modenese (Giovanni Guerra) e un corrispondente ferrarese (Ercole Provenzale) in un grande spettacolo romano a difesa di Galilei: l’Amor Pudico (1614) - Elena Tamburini (Annali Online dell'Università di Ferrara. Sezione Lettere)
An important festival for the wedding of Prince Michele Peretti and Princess Anna Maria Cesi was held in Rome in 1614. From many aspects this was an extraordinary festival, with lots of dancing, but surely not only. So far not much attention has been given to this important event. The bridegroom was a brother of Cardinal Montalto (and thus a descendant of Pope Sisto V) vice-chancellor and a very influential member of the “Ac-cademia degli Umoristi”. The bride was a cousin of Prince Federico Cesi, who was the founder and leading person of the “Accademia dei Lincei”. It was unavoidable that during this festi-val the life and the subsequent tensions in both Academies came to light, which created heated discussions among those present. This led, of course, to further discussions and strain. Consid-ering the period this was doubtless very courageous since these two Academies had the intention to use this festival for defending Galilei and the Nuova Scienza. Among the numerous per-sons who collaborated were two artists forming part of the Este culture, viz Giovanni Guerra, an architect and painter, responsible for the theatre and probably also for the costumes and Ercole Provenzale, an Enzo Bentivoglio’s correspondent to whom we owe much and authentic information on this event.